The Greek crisis: Causes and consequences - Antonio I. Garcia Pascual; Piero Ghezzi (Center for Economic Studies and ifo Institute (CESifo), 2011)
Greece has reached a point where, under any plausible macroeconomic scenario, public debt will continue growing faster than GDP. Fiscal consolidation alone cannot close the solvency gap. A substantial reduction in the stock of debt is needed. Even post-debt restructuring, there is no guarantee that the government will succeed in its dual goal of restoring fiscal solvency and closing the competitiveness gap. Yet we think Greece stands a better chance of accomplishing these goals from inside the EMU rather than outside it. This chapter takes stock of the factors that led to the explosion of public debt, the loss of competitiveness, and the failure of the first EU-IMF programme. We also present our views on the likely debt restructuring (and post-restructuring) scenarios.
Keywords: E60; F40; 330; Öffentliche Schulden; Staatsbankrott; Internationaler Wettbewerb; Umschuldung; Haushaltskonsolidierung; Griechenland; Schuldenübernahme; EU-Staaten; Welt